Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Sure! To solve the pair of simultaneous equations:
[tex]\[ \begin{array}{c} 3x + y = 19 \quad \quad \text{(1)}\\ x - y = 1 \quad \quad \text{(2)} \end{array} \][/tex]
Here's a detailed step-by-step solution:
1. Isolate \( y \) in the second equation.
From equation (2):
[tex]\[ x - y = 1 \][/tex]
We can solve for \( y \) by adding \( y \) to both sides and then subtracting 1 from both sides:
[tex]\[ x - 1 = y \][/tex]
So, we have:
[tex]\[ y = x - 1 \][/tex]
2. Substitute \( y = x - 1 \) into the first equation.
Replace \( y \) in equation (1) with \( x - 1 \):
[tex]\[ 3x + (x - 1) = 19 \][/tex]
3. Simplify the resulting equation to find \( x \).
Combine like terms:
[tex]\[ 3x + x - 1 = 19 \implies 4x - 1 = 19 \][/tex]
Next, add 1 to both sides:
[tex]\[ 4x = 20 \][/tex]
Finally, divide both sides by 4:
[tex]\[ x = 5 \][/tex]
4. Substitute \( x = 5 \) back into \( y = x - 1 \).
Using the expression for \( y \):
[tex]\[ y = 5 - 1 \][/tex]
So, we get:
[tex]\[ y = 4 \][/tex]
5. Verify the solution.
Substitute \( x = 5 \) and \( y = 4 \) back into the original equations to ensure they are true:
For equation (1):
[tex]\[ 3(5) + 4 = 15 + 4 = 19 \][/tex]
For equation (2):
[tex]\[ 5 - 4 = 1 \][/tex]
Both original equations are satisfied with \( x = 5 \) and \( y = 4 \).
So, the solution to the system of equations is:
[tex]\[ (x, y) = (5, 4) \][/tex]
[tex]\[ \begin{array}{c} 3x + y = 19 \quad \quad \text{(1)}\\ x - y = 1 \quad \quad \text{(2)} \end{array} \][/tex]
Here's a detailed step-by-step solution:
1. Isolate \( y \) in the second equation.
From equation (2):
[tex]\[ x - y = 1 \][/tex]
We can solve for \( y \) by adding \( y \) to both sides and then subtracting 1 from both sides:
[tex]\[ x - 1 = y \][/tex]
So, we have:
[tex]\[ y = x - 1 \][/tex]
2. Substitute \( y = x - 1 \) into the first equation.
Replace \( y \) in equation (1) with \( x - 1 \):
[tex]\[ 3x + (x - 1) = 19 \][/tex]
3. Simplify the resulting equation to find \( x \).
Combine like terms:
[tex]\[ 3x + x - 1 = 19 \implies 4x - 1 = 19 \][/tex]
Next, add 1 to both sides:
[tex]\[ 4x = 20 \][/tex]
Finally, divide both sides by 4:
[tex]\[ x = 5 \][/tex]
4. Substitute \( x = 5 \) back into \( y = x - 1 \).
Using the expression for \( y \):
[tex]\[ y = 5 - 1 \][/tex]
So, we get:
[tex]\[ y = 4 \][/tex]
5. Verify the solution.
Substitute \( x = 5 \) and \( y = 4 \) back into the original equations to ensure they are true:
For equation (1):
[tex]\[ 3(5) + 4 = 15 + 4 = 19 \][/tex]
For equation (2):
[tex]\[ 5 - 4 = 1 \][/tex]
Both original equations are satisfied with \( x = 5 \) and \( y = 4 \).
So, the solution to the system of equations is:
[tex]\[ (x, y) = (5, 4) \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.